Reframing Central American Migration From Narrative Journalism. (January 2019) - Palau-Sampio, Dolors
Over the past decade, some journalists and media have addressed Central American migration to the United States from an investigative and narrative reporting perspective, providing a more reliable and accurate portrait of the main characters and their underlying reasons for making the move. This article examines how an ethnographic and analytical approach in combination with narrative techniques can improve the coverage of complex issues such as migration, providing more detailed and complete information than conventional media presents. The qualitative analysis focuses on five projects, including the crossmedia On the Road —with a long-form reportage, a book of photographs, and a documentary—and four multimedia documents released by Central American platforms, in some cases in partnership with U.S. media and foundations. The results emphasize that new reporting techniques and coverage inspired in slow journalism can help to reframe migration in a radically different way.